Supercluster characterization in cosmological simulations (2018)
We compare cosmological simulations of N-bodies with the results obtained by Tully et al. (2014) to determine the shape, mass and size of Laniakea, our local supercluster. Continuing the work done by Hernandez (2016) in determining the significance of Laniakea in these simulations, we implement the Watershed algorithm to reconstruct and segregate the superclusters. We find that Laniakea is an atypical event in terms of shape, volume and mass in the framework of cosmological simulations.